2002
DOI: 10.1161/01.cir.0000015862.64816.b2
|View full text |Cite
|
Sign up to set email alerts
|

Biological Gradient Between Long-Term Arsenic Exposure and Carotid Atherosclerosis

Abstract: Background-Long-term exposure to ingested arsenic has been documented to induce peripheral vascular disease, ischemic heart disease, and cerebral infarction in a dose-response relationship. This study further examined the biological gradient between ingested inorganic arsenic and carotid atherosclerosis. Methods and Results-We studied 199 male and 264 female adult residents from the southwestern area of endemic arseniasis in Taiwan. The extent of carotid atherosclerosis was assessed by duplex ultrasonography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(131 citation statements)
references
References 28 publications
9
120
0
Order By: Relevance
“…The finding of a strikingly increased prevalence of macrovascular diseases observed in the arseniasis-endemic area compared with the nonendemic area is consistent with our previous findings of arsenic-induced atherosclerosis (Chen et al 1988bChiou et al 1997b;Tseng et al 1996;Wang et al 2002;Wu et al 1989). There have been few studies comparing the prevalence of specific vascular diseases in relation to arsenic exposure in diabetics and nondiabetics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding of a strikingly increased prevalence of macrovascular diseases observed in the arseniasis-endemic area compared with the nonendemic area is consistent with our previous findings of arsenic-induced atherosclerosis (Chen et al 1988bChiou et al 1997b;Tseng et al 1996;Wang et al 2002;Wu et al 1989). There have been few studies comparing the prevalence of specific vascular diseases in relation to arsenic exposure in diabetics and nondiabetics.…”
Section: Discussionsupporting
confidence: 92%
“…Diabetes was associated with an increased risk of cerebrovascular disease showing an age-and gender-adjusted odds ratio of 1.8 in the northeastern endemic area and 2.4 (21.35 ÷ 8.72) in the southwestern endemic area of this study. A previous study showed a dose-response relationship between ingested arsenic and peripheral vascular diseases (Wang et al 2002). The present study demonstrated the odds ratios of 1.2 (95% CI, 1.1-1.4) in diabetics and 12.5 (95% CI, 9.5-16.5) in nondiabetics.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Consistent with the association with risk factors and CV disease, an association has also been found between As exposure and atherosclerosis (Wang et al 2002;Wang et al 2010;Hsieh et al 2011), and confirmed in experimental animal studies (Bunderson et al 2004;Srivastava et al 2009;Lemaire et al 2011). …”
Section: As In the CV Continuumsupporting
confidence: 64%
“…Epidemiological studies analyzing the correlation between cardiovascular diseases and arsenic exposure, have linked arsenic to atherosclerosis (Wang et al, 2002), ischemic heart disease (Tseng et al, 2003) and hypertension (Rahman et al, 1999). Drinking water is a significant source of arsenic exposure to humans.…”
Section: Introductionmentioning
confidence: 99%